Cultura e educação das comunidades ciganas: a oferta do ensino público gratuito para as suas crianças e adolescentes em Itumbiara/GO - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This research addresses the ethnic relations of gypsies who settled in Itumbiara and enrolled their children in the municipal public network, with the main problem being the non-literacy of gypsy students in the municipality, characterizing non-compliance with strategy 3.4 of the Municipal Education Plan (PME). The objectives include identifying the literacy process of Roma students according to PME strategy 3.4, understanding the inclusion of their particularities in educational practices, exploring the contribution of teacher training to literacy and identifying the factors that impede this process. The methodology adopted is an exploratory case study, accompanied by a bibliographic review on the historical-cultural trajectory of gypsy people, focusing on heterogeneity, culture, identity, and history of gypsies in Brazil. The research is limited to five municipal school units in different locations in Itumbiara, all with students belonging to the gypsy ethnicity. Studies on the gypsy ethnicity cover diverse themes, including historical, social issues, ethnic dynamics and their interactions, with references from authors such as: (Teixeira, 1998; Moonen, 2011; Fazito, 2000; Woodward, 2004; Nisbet, 1967; Agamben ,2015; Renan, 1997; Rodriguez, 2011; Donovan, 1992; Costa, 1997; Le Goff, 2013; Rodrigo Teixeira, 2008). To support the importance of guaranteeing free public education, the full exercise of citizenship and literacy as a crucial element for cultural empowerment and active participation in society, we used (Libâneo, 2004; Cury, 2002; Carvalho, 2002; Soares, 2020; Mortatti, 2016). Data analysis will be conducted through the authors, (Yin, 2005; Flick, 2004; Stake, 1999; Dooley 2002; Minayo, 2001). Historical information about gypsy communities in Itumbiara is scarce, increasing interest, especially in the context of public education and these children's right to literacy. The research is highly relevant to society, academia and schools, highlighting the need for effective policies to overcome the challenges faced by Roma students.
Culture and education of gypsy communities: the offer of free public education for their children and adolescents in Itumbiara/GO
Keywords: Etnia cigana; Alfabetização; Ensino público; Public education; Gypsy ethnicity; Literacy; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::EDUCACAO